Pathways of methane removal in the sediment and water column of a seasonally anoxic eutrophic marine basin - Żygadłowska, Olga M.; Venetz, Jessica; Klomp, Robin; Lenstra, Wytze K.; van Helmond, Niels A. G. M.; Röckmann, Thomas; Wallenius, Anna J.; Martins, Paula Dalcin; Veraart, Annelies J.; Jetten, Mike S. M.; Slomp, Caroline P. (Frontiers in Marine Science, 2023)
Methane (CH4) is a key greenhouse gas. Coastal areas account for a major proportion of marine CH4 emissions. Eutrophication and associated bottom water hypoxia enhance CH4 production in coastal sediments. Here, we assess the fate of CH4 produced in sediments at a site in a seasonally anoxic eutrophic coastal marine basin (Scharendijke, Lake Grevelingen, the Netherlands) in spring (March) and late summer (September) in 2020. Removal of CH4 in the sediment through anaerobic oxidation with sulfate (SO42-) is known to be incomplete in this system, as confirmed here by only slightly higher values of δ13C-CH4 and δD-CH4 in the porewater in the shallow sulfate-methane-transition zone ( 5-15 cm sediment depth) when compared to deeper sediment layers. In March 2020, when the water column was fully oxygenated, CH4 that escaped from the sediment was at least partially removed in the bottom water through aerobic oxidation. In September 2020, when the water column was anoxic below 35 m water depth, CH4 accumulated to high concentrations (up to 73 µmol L-1) in the waters below the oxycline. The sharp counter gradient in oxygen and CH4 concentrations at 35 m depth and increase in δ13C-CH4 and δD-CH4 above the oxycline indicate mostly aerobic water column removal of CH4. Water column profiles of particulate and dissolved Fe and Mn suggest redox cycling of both metals at the oxycline, pointing towards a potential role of metal oxides in CH4 removal. Water column profiles of NH4+ and NO3- indicate removal of both solutes near the oxycline. Analyses of 16S rRNA gene sequences retrieved from the water column reveal the presence of aerobic CH4 oxidizing bacteria (Methylomonadaceae) and anaerobic methanotrophic archaea (Methanoperedenaceae), with the latter potentially capable of NO3- and/or metal-oxide dependent CH4 oxidation, near the oxycline. Overall, our results indicate sediment and water column removal of CH4 through a combination of aerobic and anaerobic pathways, which vary seasonally. Some of the CH4 appears to escape from the surface waters to the atmosphere, however. We conclude that eutrophication may make coastal waters a more important source of CH4 to the atmosphere than commonly assumed.